2022
DOI: 10.1155/2022/4913031
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Nerve Parameter Reference Values for Chinese Adults Assessed by Corneal Confocal Microscopy

Abstract: Background. Confocal corneal microscopy is an excellent new noninvasive tool for assessing diabetic peripheral neuropathy. We aimed to investigate the clinical variables associated with corneal nerve parameters and establish reference values for clinical use in healthy Chinese adults. Methods. The study enlisted 257 healthy volunteers (137 females and 120 males) from two clinical academic centers in China. Two experts captured and selected images of the central corneal subbasal nerve plexus at each center usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…CNFL was the next most commonly studied parameter, with 2 studies demonstrating negative correlations between CNFL and advancing age, which is in line with our results. 20,23 CNFrD is a rather new automated nerve metric, which measures the topological complexity of main nerve fibers and branches. 42 It is expressed as a ratio of the logarithm of the total number of boxes that contain nerve fibers to the logarithm of the number of boxes of the image width.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNFL was the next most commonly studied parameter, with 2 studies demonstrating negative correlations between CNFL and advancing age, which is in line with our results. 20,23 CNFrD is a rather new automated nerve metric, which measures the topological complexity of main nerve fibers and branches. 42 It is expressed as a ratio of the logarithm of the total number of boxes that contain nerve fibers to the logarithm of the number of boxes of the image width.…”
Section: Discussionmentioning
confidence: 99%
“…17 Current studies have shown inconsistent results of the age effects on corneal nerves, with some demonstrating adverse effects of age on corneal nerve morphology such as decreasing subbasal nerve fiber density with age, [18][19][20] while others demonstrate no statistically significant changes in nerve fiber density, branch density, and length with age. [21][22][23] Regarding the corneal epithelium, Gambato et al and Niederer et al showed that there was no change in mean cell density of basal epithelial cells with age using IVCM evaluation. 21,24 Another study showed that a decrease in the density of limbal basal epithelial cells was observed with age because of the deteriorating proliferative ability with age, leading to a decrease in corneal epithelial thickness, although the central corneal epithelium was less susceptible to these age-related changes.…”
mentioning
confidence: 99%